The Impact of visual perspectives in advertisements on consumers' reactions to close-to-expiry food - Meng, Lu (Journal of business ethics, 2025)
Food waste presents an escalating environmental and social challenge to the establishment of a sustainable marketing system and the long-term development of our society. Given the substantial volume of food wasted due to the rejection of close-to-expiry food, this study explores how visual perspectives influence consumers’ reactions to close-to-expiry food. Specifically, we find that a third-person (vs. first-person) perspective in advertisements enhances consumers’ positive reactions to close-to-expiry food. This effect is driven by the heightened level of other-focus elicited by the third-person perspective and is mitigated when consumers’ level of self-construal misfits with visual perspectives in terms of the direction of other-focus elicited or when the food item is far from expiry. These findings contribute to research on close-to-expiry food marketing, visual perspectives, other-focus, and consumer ethics. Furthermore, the current research provides critical implications for various stakeholders and society as a whole.